The Role of Influencer-Generated Contents to the Cognition and Emotional Attachment Among Generation Z Consumers in Manila, Philippines - Angeles, Rhea Jane G.; Clemente, Carmhiella A.; Malimban, Renoa Lorraine O.; Santos, Jean Erika G.; Tan, Jian Carlo D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Along with the rising digitalization of businesses, social media influencers (SMI) have been essential in redefining how the online promotional system operates. In the Philippines alone, social media influencers are central to all online discussions. The country is known as the "social media capital of the world," as 86.3% of Filipinos follow at least one influencer and spend about 11 hours each week on social media. With the use of an existing theory and testable hypotheses, the researchers will gather data while adhering to the positivist philosophy. To obtain objective and statistically significant results, the researchers will measure, document, and examine the data through a survey. Moreover, the researchers will carry out various statistical testing, including PLS-SEM, average variance extraction (AVE), heterotrait-monotrait (HTMT) ratio, variance inflation factor (VIF), squared multiple correlation (R2), Stone–Geisser’s Q2, etc. using SmartPLS. Delving into the results, it was shown that influencer-branded content's interestingness does affect users to be emotionally attached. Research findings also revealed that influencer-generated content's novelty does not significantly affect users' emotional attachment to influencers. It was also shown that reliability positively affects emotional attachment, as well as information quality. But when it comes to understandability it shows no relationship with emotional attachment. Lastly, it is revealed that there is no significant relationship between emotional attachment and users' intention to disagree with the influencer. As a conclusion, social media influencers have become instrumental in making digital platforms a more enjoyable place to dwell.